A THEORETICAL ESTIMATION OF PERFORMANCE PROPERTIES COATINGS BASED ON Fe-Cr-B-Si WITH LASER MELTING AND ALLOYING (World Science, 2016)
The surface hardening of laser of powder coat the system Fe-Cr-B-Si to permit lower wear of the coat. The theory of resistence of wear of the laser based an analisis strengthening of interection of atoms complex particles of the powder and detail we showed the influence of the speed of ray and diameter of stain of the laser. The theory and experiments of BNTU (Minsk) showed satisfactorily agreement for the system Fe-Cr-B-Si. This theory is the base of nanotechnology of the laser.